Genetic coefficients of sugarcane phenology traits for crop model refinement - Ngobese, Immaculate (University of the Free State, 2015)
Crop models provide a simulation of crop growth and development through the use of mathematical equations and have substantial potential as research tools. They can assist breeding by predicting complex traits (e.g. sucrose yield) through simulating interactions between simple genetic traits (e.g. leaf elongation rate per unit thermal time) and environmental factors (e.g. temperature). The Canegro sugarcane model uses cultivar coefficients to simulate the effects of genotype, environment, and management on crop performance. The current coefficients in the Canegro model are limited to data from the cultivar NCo376 and estimates for a wider range of cultivars are not available for key growth parameters. The primary objective of this study was to quantify the cultivar coefficient values for some tillering and stalk elongation, leaf phenology, and biomass production traits for a diverse range of sugarcane cultivars. An additional objective was to determine the stability and heritability of these traits across environments and crop stages to determine their potential contribution to future model-assisted breeding. Cultivar trials were established at three separate sites on South African Sugarcane Research Institute (SASRI) research farms; Amatikulu (AK), Pongola (PG), and Bruynshill (BH). The same set of 12 cultivars was tested at the three sites. The trials were planted in randomized complete block designs with four replications. The following cultivar traits were determined from within-season growth measurements: peak tiller population (PTP); thermal time to peak tiller population (TTPP); final population (FPOP); tiller survival percentage (TSP); stalk elongation rate (SER); leaf appearance rate (LAR); maximum leaf area (LAmax); thermal time to maximum leaf area (TTLAmax); maximum leaf number (LFmax); and leaf area index (LAI). Cane yield, estimated recoverable crystal percent (ERC%), ERC yield, total biomass, and brown (dead), and green leaf material were determined at each harvest. Plant and first ratoon crops were harvested at AK and PG, while only the plant crop was harvested at BH. The data were analysed using GENSTAT to estimate the variance components associated with cultivar, site, crop, and their interactions. Broad-sense heritability was calculated for each trait. Cultivar rank correlations across sites and across crops within sites were evaluated as a measure of trait stability. The highly significant (P<0.01) effect of cultivar (C) was larger than the cultivar x ratoon (C x R) and cultivar x site (C x S) effects for most traits. Mean trait values for most traits differed significantly between sites and ratoons within sites. Cultivars generally showed consistent rankings for PTP, TSP, SER, LAR, LAmax, LAI, and ERC% across sites for individual crops. Cultivars also showed consistent rankings across ratoons within a site for PTP, FPOP, SER, LAmax, LAR, LFmax, LAI, ERC%, cane yield, and ERC yield. This suggests that some traits are stable and can therefore be used for model-wise exploration of genotype by environment (G x E) interactions in sugarcane. Also, it may be feasible to characterise cultivars for some traits from single-site and single-ratoon experiments in the future. Some cultivars were identified as ideal indicator cultivars for future characterisation studies. Broad sense heritability estimates ranged from 0 to 0.99 for all traits studied. The FPOP, PTP, SER, LAR, LFmax, LAmax, LAI, cane yield, ERC%, and total biomass had high broad sense heritability estimates. These traits are therefore largely genetically controlled and can be selected for in a breeding programme. The cultivar coefficient values determined here will be incorporated into the Canegro crop model and help refine the model’s ability to simulate cultivar growth differences across environments. The range of values determined for these traits will also contribute to model-wise exploration of G x E interactions and future model-assisted breeding efforts for sugarcane.

Gewasmodelle verskaf ‘n simulasie van gewasgroei en ontwikkeling deur die gebruik van wiskundige vergelykings en het groot potensiaal as navorsingshulpmiddel. Dit kan teling ondersteun deur komplekse eienskappe te voorspel (bv. sukrose opbrengs) vanaf interaksies tussen eenvoudige genetiese eienskappe (bv. blaar verlengingstempo per eenheid hitte tyd) en omgewingsfaktore (bv. temperatuur). Die Canegro suikerriet model gebruik cultivar koeffisiente om die effek van genotipe, omgewing en bestuur op gewasproduktiwiteit te simuleer. Die huidige koeffisiente in die Canegro model word beperk tot data van die cultivar NCo376 en skattings vir ‘n wyer reeks van cultivars is nie beskikbaar vir sleutel groei parameters nie. Die primêre doel van hierdie studie was om cultivar koeffisiënt waardes te kwantifiseer vir sekere stoel en stam verlengings eienskappe, blaar fenologie, en biomassa produksie eienskappe vir ‘n diverse reeks suikerriet cultivars. ‘n Addisionele doel was om die stabiliteit en oorerflikheid van hierdie eienskappe oor omgewings en gewasstadiums te bepaal om hulle potensiële bydrae tot toekomstige model-ondersteunde teling vas te stel. Drie cultivarproewe is gevestig by drie omgewings op SASRI navorsingsplase; Amatikulu (AK), Pongola (PG) en Bruynshill (BH). Dieselfde stel van 12 cultivars is getoets by die drie omgewings. Die proewe is geplant in gerandomiseerde blokontwerpe met vier herhalings. Die volgende cultivar eienskappe is bepaal van binne-seisoen groei metings: piek stam populasie (PTP); hittetyd tot piek stam populasie (TTPP); finale populasie (FPOP); stam oorlewings persentasie (TSP); stam verlengingstempo (SER); blaar verskyningstempo (LAR); maksimum blaararea (LAmax); hittetyd tot maksimum blaararea (TTLAmax); maksimum getal blare (LFmax); en blaararea indeks (LAI). Rietopbrengs, geskatte herwinbare kristal persentasie (ERC%), ERC opbrengs, totale biomassa, en bruin (dooie) en groen blaarmateriaal is is bepaal by elke oes. Plant en eerste ratoen gewasse is geoes by AK en PG, terwyl net plant gewas geoes is by BH. Die data is geanaliseer met GENSTAT om die variansie komponente geassosieer met cultivar, omgewing, gewas en hulle interaksies te bepaal. Breë sin oorerflikheid is vir elke eienskape bereken. Cultivar rangorde korrelasies oor omgewings en gewasse is geëvalueer as ‘n meting van eienskap stabiliteit. Die hoogs betekenisvolle (p<0.01) effekte van cultivar (C) was groter as die van cultivar x ratoen (C x R) en cultivar x omgewings (C x S) effekte vir meeste eienskappe. Gemiddelde eienskap waardes vir meeste eienskappe het betekenisvol verskil tussen omgewings en ratoene binne omgewings. Cultivars het oor die algemeen konstante rangordes getoon vir PTP, TSP, SER, LAR, LAmax, LAI en ERC% oor omgewings en individuele gewasse. Cultivars het ook konstante rangordes oor ratoens binne ‘n omgewing vir PTP, FPOP, SER, LAmax, LAR, LFmax, LAI, ERC%, riet opbrengs en ERC opbrengs getoon. Dit dui aan dat sommige eienskappe stabiel is en dat hulle gebruik kan word vir model-wyse ondersoeke van genotipe by omgewing (G x E) interaksie in suikerriet. Cultivars mag ook gekarakteriseer word vanaf enkel omgewing en enkel-ratoen proewe in die toekoms. Sommige cultivars is geïdentifiseer as ideaal vir toekomstige karakteriserings studies. Breë sin oorerflikheidsskattings het gewissel van 0 tot 0.99 vir alle eienksappe. Die FPOP, PTP, SER, LAR, LFmax, LAmax, LAI, rietopbrengs, ERC% en totale biomassa het hoë breë sin oorerflikheid getoon. Hierdie eienskappe word daarom grootliks geneties beheer en kan geselekteer word in telings programme. Die cultivar koefissiënte wat hier bepaal is sal in die Canegro gewasmodel geïnkorporeer word en sal help om die model se vermoë te verfyn om cultivar groeiverskille te simuleer oor omgewings. Die waardes wat bepaal is vir die gemeette eienskappe sal ook bydra tot model gebasseerde ondersoek van G x E interaksies en toekomstige model-ondersteunde teling in suikerriet.
Dissertation (M.Sc. (Plant Breeding (Agronomy))--University of the Free State, 2015
Keywords: Cultivar trials; Canegro model; Cultivar coefficient; Leaf phenology